(3TQM GddeYIs - (3GdHjGJj, GdfLaj, GdCMeOj, edG cJGH, eMeO LhGO Hf eMeO Jbj Hf eMeO, (B( (3cGf MjG (B1267 (3g` (B)s
(3ChdgG (B:s
(3GdMeO ddg (B...(3LYdJ cJGHj gPG LGQjG eLQi GdTQM dg eaUdG deG CLedg hde CLYdg eYdbG Ydi ZjQg ef GdcJH GdeWhdI dcKQI GdThGZd hMOhK GdfhGRd hJThjT GdHGd hVjb GdeLGd (B...s
(3BNQgG (B:s
... (3eG PgH Edjg ef YOe JWgjQ Gdbdjd GdeSJYed aj GdWgGQI GdcHQi dcf GdMce HGdcQGgI Ch GdHWdGf dPdc ZjQ eJLg SqjeG EPG cGf GdeGA eedhcG ddeZJSd (B...s
(3HNW bOje MJi GdhQbI (B81 (3Ke HNW eZGjQ MOjKs
(3JHUQI GdYfhGf (B:s
(3PcQ Bb HQRc WgQGfj GNJdGa YfhGf GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\201s
(3GdPQjYI (B2 - 243 ( 1700)s
Keywords: (3abg GdePGgH GdCNQis